Electricity market options for heat pumps in rural district heating networks in Austria. (1st April 2020) - Terreros, O.; Spreitzhofer, J.; Basciotti, D.; Schmidt, R.R.; Esterl, T.; Pober, M.; Kerschbaumer, M.; Ziegler, M.
Abstract: The integration of renewable heat sources in the electricity grid represents a challenge in the energy system due to their stochastic production character. Besides, the rural district heating sector in Austria is confronted with a large number of biomass boilers reaching the end of their lifetime and thus operating unprofitably. In this context, heat pumps have a decisive role in supporting both networks and providing flexibility. However, their implementation is not yet extended in Austria. This paper shows the potential of heat pump utilization in several concrete use cases. Results determine that heat pumps can be active players in the Austrian electricity market. Energy costs can be saved by taking advantage of low prices in the day-ahead market and additional revenues can be earned in the balancing market. Offering negative balancing energy for the automatic frequency restoration reserve (aFRR) presents a potentially interesting business case since it provides a considerable reduction in the heat generation costs. Considering the complexity and uncertainty of the future market development, awareness on the most influencing factors gains great relevance. Results show that fluctuations in the biomass price and call probabilities can affect the heat pump profitability. Highlights: Heat pumps can improve the profitability of old rural district heating networks. The optimal bidding strategy offers negative balancing energy for aFRR. Heat generation costs are reduced by 17, 7% (flue gas) and 27, 5% (sewage water). Use cases with flue gas show the best profitability (LCOE reduced by 6, 7%).